Measurements of user and sensor data from the Internet of Things (IoT) devices - Ometov, Aleksandr (2022)
The evolution of modern cyber-physical systems and the tremendous growth in the number of interconnected Internet of Things (IoT) devices are already paving new ways for the development of improved data collection and processing methods [...]